Chains of trust - Bajt, Veronika (Anthropological notebooks, 2018)
This article analyses the case of Slovenia, a post-socialist state with a notable history of state social interventions and institutionalised care. Nowadays, however, flexibilisation rules the labour market, and activation is the primary social policy measure, according to which benefits become conditioned upon inclusion into paid labour, and the state only intervenes in cases of severe poverty. In recent years, alongside changes in social policy, the state has introduced measures against illicit work, including work in private households. The demand for care work is growing, while it is increasingly being relegated to the private domain. Drawing on interviews with informal care workers, we delineate methodological concerns related to conducting qualitative research, arguing that the individualisation of care work has brought increased state control and, in consequence, fear among and marginalisation of care workers. Introducing the concept of chains of trust, the article concludes that the structural effect of the individualisation of care is seclusion behind the four walls of private households, where trust becomes the only currency.
Keywords: individualizacija skrbi; neformalno delo; skrb; Slovenija; zaupanje